Kontradiktif Perkawinan Beda Agama Perspektif Undang-Undang Perkawinan dan Undang-Undang Administrasi Kependudukan - Ditta Giarni Martha (Indra Institute Research & Publication, 2024)
This research aims to examine the philosophical basis for the formation of the Marriage Law and the Population Administration Law in regulating interfaith marriages. This research uses a method using study literature, namely a method by collecting data from previous research results regarding interfaith marriages and processing the data to analyze it on the philosophical basis of the Marriage Law and the Population Administration Law. The results of this research show that in the Marriage Law the existence of the Marriage Law jo. Government Regulation no. 9 of 1975. Article 2 paragraph (1) of the Marriage Law clearly stipulates that: